ANALISIS PENDAPATAN USAHATANI BAWANG MERAH (ALLIUM ASCALONICUM) DI DESA SEI.GERINGGING KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR - Herlita, Mona; Tety, Ermi; Khaswarina, Shorea (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research are: 1) know the onion cultivation, 2) analyse the income of onion farming, and 3)know the management of onion farming in Sei. Geringging Village Kampar Kiri District Kampar Regency. This research conducted since April till July 2014. The samples in this research used random sampling method, namely taking a random sample of the population of onion farmers as much as 20 peoples. Onion cultivation in Sei. Geringging Village still conventional. Pre-planting treatment undertaken is tillage, then planting with a spacing of 15 x 15 cm. Fertilizers used in this farming are organic and inorganic fertilizers. Maintenance of onion farming includes the watering step and weeding step. Onion harvest is done when the age of onion plants 60 days old after planting. The analysis in this research are the gross revenue, production cost, net income, farm efficiency, and farm management. Gross revenue of onion farming is Rp.490.000.000, while production costs amounted to Rp.321.258.734, then net income of onion farming amounted to Rp.168.741.266 per 4 ha with RCR value amounted to 1,53, it means every Rp.1 cost will earn revenues of Rp.1,53, thus indicated that onion farming in Sei. Geringging Village economically efficient and feasible to be continued and developed. Management of onion farming in Sei. Geringging Village good enough, but there are some management functions that must be considered again such as the controlling function must be aware again. Â Keywords: Onion Farming, Cultivation, Income, Management